2018
DOI: 10.15587/2312-8372.2018.141248
|View full text |Cite
|
Sign up to set email alerts
|

Development of a complex bakery improver «Freshness SMS Super» to extend the freshness of wheat bread

Abstract: Об'єктом дослiдження у роботi є пшеничний хлiб, одним з найбiльших недолiкiв якого є черствiння пiд час зберiгання. Iнтенсивнiсть перебiгу процесiв в готовому виробi, що зумовлюють черствiння, залежать вiд якостi сировини, зокрема хлiбопекарських властивостей борошна. Вирiшення проблеми подовження свiжостi пшеничного хлiба можливе використанням нетрадицiйної сировини, харчових добавок та комплексних хлiбопекарських полiпшувачiв. В ходi розроблення комплексного хлiбопекарського полiпшувача «Свiжiсть СМС Супер» … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…It was found that in the development of a complex bakery improver, the rational dosage of DW is 2 % by weight of flour [9], and WPC -3 % by weight of flour [4]. In further studies, it is advisable to reveal the effect of DW and WPC on the structural and mechanical properties of the dough for the logical choice of food additives in the active part of the improver.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that in the development of a complex bakery improver, the rational dosage of DW is 2 % by weight of flour [9], and WPC -3 % by weight of flour [4]. In further studies, it is advisable to reveal the effect of DW and WPC on the structural and mechanical properties of the dough for the logical choice of food additives in the active part of the improver.…”
Section: Introductionmentioning
confidence: 99%